MHealth and Collecting Research Data From Patients With Mobile Tablet Apps. Issue 6 (November 2015) - McCartney, Patricia
Abstract : There are many opportunities for researchers for using mobile tablet apps to engage patients and collect data. Our IT expert, Dr. McCartney, explains the latest on this exciting trend.